The acute effects of heavy-load squats and loaded countermovement jumps on sprint performance - McBride, J. M.; Nimphius, S.; Erickson, T. M. (The Journal of Strength and Conditioning Research, 2005)
The purpose of this investigation was to determine whether performing high force or explosive force movements prior to sprinting would improve running speed. Fifteen NCAA Division III football players performed a heavy-load squat (HS), loaded countermovement jump (LCMJ), or control (C) warm-up condition in a counterbalanced randomized order over the course of 3 weeks. The HS protocol consisted of 1 set of 3 repetitions at 90% of the subject's 1 repetition maximum (1RM). The LCMJ protocol was 1 set of 3 repetitions at 30% of the subject's 1RM. At 4 minutes post-warm-up, subjects completed a timed 40-m dash with time measured at 10, 30, and 40 m. The results of the study indicated that when preceded by a set of HS, subjects ran 0.87% faster (p 0.05) in the 40-m dash (5.35 ± 0.32 vs. 5.30 ± 0.34 seconds) in comparison to C. No significant differences were observed in the 10-m or 30-m split times between the 3 conditions. The data from this study suggest that an acute bout of low-volume heavy lifting with the lower body may improve 40-m sprint times, but that loaded countermovement jumps appear to have no significant effect.